2021
DOI: 10.1530/jme-20-0229
|View full text |Cite
|
Sign up to set email alerts
|

Obesity enhances the recruitment of mesenchymal stem cells to visceral adipose tissue

Abstract: In obesity, high levels of TNF-α in the bone marrow microenvironment induces the bone marrow-mesenchymal stem cells (BM-MSCs) towards a pro-adipogenic phenotype. Here, we investigated the effect of obesity on the migratory potential of BM-MSCs and their fate towards the adipose tissues. BM-MSCs were isolated from male C57Bl/06 mice with high-fat diet-induced obesity. The migratory potential of the BM-MSCs, their presence in the subcutaneous (SAT) and the visceral adipose tissues (VAT), and the possible mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…In our studies, hAD-MSCs were used at the third passage in the experiments, and the hAD-MSC population from different clones was proven to stably express the CXCR4 protein. The results confirm the abundant CXCR4 expression in hAD-MSCs, similar to CXCR4 expression in other types of MSCs [24,35,62].…”
Section: Discussionsupporting
confidence: 82%
“…In our studies, hAD-MSCs were used at the third passage in the experiments, and the hAD-MSC population from different clones was proven to stably express the CXCR4 protein. The results confirm the abundant CXCR4 expression in hAD-MSCs, similar to CXCR4 expression in other types of MSCs [24,35,62].…”
Section: Discussionsupporting
confidence: 82%
“…A Brazilian group demonstrated that [ 174 ] inflammatory cytokines—TNF alpha in particular—are able to induce the expression of CXCR4 on MSCs, which gives a plausible explanation of their enhanced migration in animal models of obesity. Moreover, leptin and interleukin-10 (IL-10) were found to be increased in visceral but not in subcutaneous WAT from obese mice, confirming site-dependent variations in the MSC microenvironment [ 21 ]. A high-fat diet is also demonstrated to promote adipogenesis and inhibit osteogenesis through leptin receptor signaling in bone marrow MSCs [ 175 ].…”
Section: Msc Function and Obesitymentioning
confidence: 99%
“…ADSC function is regulated by the tissue microenvironment: obesity, hypoxia and inflammation affect ADSC cellular plasticity and alter their immunophenotypic profile and regenerative functions [ 20 ]. In addition, obesity enhances their migratory potential and leads to their accumulation in visceral adipose tissue (VAT) [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The proliferative actions of these cells were discovered as secondary effects of leptin secretion [2][3][4]. Adipose tissue is distributed normally around the body at sites such as the bone marrow (i.e., red adipose) [5], articular cartilage, and visceral and subcutaneous fat deposits [6][7][8][9][10]. Adipose tissue may also form around the hepatic tissue [11] and cardiac smooth muscle [12].…”
Section: The Anatomy Of Adipose-tissue-derived Stem Cells (Adsc)mentioning
confidence: 99%